Teachers' beliefs and English as a Second Language (ESL) teaching practices - Kartar Singh, Kulwant Kaur; Yamat, Hamidah (Penerbit UKM Press, 2019)
This book aims to unearth issues related to teachers’ beliefs about teaching and learning in the English as A Second Language (ESL) classroom. It aims to provide the most fundamental impact of ESL teaching and to provide input to enhance the quality of teaching besides identifying the strengths and weaknesses of the teachers, the students and the curriculum. The teachers’ early teaching expectations, English language learning/acquisition, attributes, challenges, passion, personality traits, the school environment, the education system and the ESL students were aspects of teachers’ beliefs that shaped their beliefs about teaching and learning in ESL classrooms. Three teachers from different years of experience were the main participants of this research as they possessed different personalities, beliefs and teaching styles that provided the depth and richness of the data collected. This study uncovered issues related to the ESL classroom through interviews, observations and document analysis The effects of the teachers’ beliefs on the teaching and learning process were also discussed and presented to reflect on what actually transpired in the ESL classroom. It is revealed that as the teaching profession is challenging, passion is essential to determine a successful ESL classroom. In addition, as experiences are related to beliefs, in-service training programmes are important to increase teacher competency and classroom management techniques are effective to facilitate and enhance learning. This book also formed a foundation for other research to enrich and improve the quality of teaching and learning in the ESL domain.